Design and characterization of chitosan-based films incorporated with summer savory (Satureja hortensis L.) essential oil for active packaging - Atlar, Cansu; Kutlu, Gozde; Tornuk, Fatih (ELSEVIER, 2024)
In this study, biodegradable films were fabricated by using cross-linked chitosan nanoparticles containing different concentrations (0, 1.0, 1.2, 1.4, and 1.5 %, v/v) of Satureja hortensis essential oil (SHEO) and their physicochemical, mechanical, antimicrobial, morphological, structural and antioxidant properties were analyzed. SHEO incorporation improved antibacterial, antioxidant and thermal properties of the films. Four studied bacteria were efficiently inhibited by films loaded with SHEO. According to the FE-SEM analysis, control film had nano-sized pores while micron sized particles were present in SHEO incorporated films. Increase in color difference was well correlated with SHEO concentration. The addition of SHEO decreased elongation at break (EB) and caused an irregular fluctuation in the tensile strength (TS) values. Increase in essential oil concentration resulted in lower water solubility. The FTIR spectra of films showed evidence of interactions and molecular arrangements when SHEO was added to the polymer matrix. Overall, the findings demonstrated that SHEO incorporated chitosan-based films were successfully prepared by cross linking and film properties were remarkably affected from SHEO concentration.
Keywords: Chitosan; Satureja hortensis L. essential oil; Edible films; Active packaging; Characterization; ANTIOXIDANT PROPERTIES; THYME; ANTIBACTERIAL; NANOPARTICLES; EXTRACTS; Biochemistry & Molecular Biology; Chemistry; Polymer Science